GAYA HIDUP KONSUMEN BARBERPOP PREMIUM DI KOTA KENDARI - Apriadi Mayoro; Ashmarita Ashmarita (Jurusan Antropologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2023)
Barberpop Premium is a barbershop/barber shop with a premium concept that affects service rates which tend to be expensive, however, Barberpop Premium has even become a popular barbershop. This study aims to describe how the lifestyle of Barberpop Premium consumers. The research method was carried out using field research techniques including the use of direct observation and interviews in data collection and analysis by qualitative descriptive method. The results of the study show that three lifestyles are carried out by every Barberpop Premium consumer. The three lifestyles are; (1) a lifestyle that shows the level of consumer social class, where consumers are more concerned with quality, comfort, and compatibility between themselves and Barberpop Premium so that consumers no longer care about high prices. (2) following fashion trends, namely consumers following fashion developments such as using skincare, choosing outfits, and visiting barbershops. (3) Hangout and shopping places for Premium Barberpop consumers, they usually hang out at premium places such as cafes and coffee shops and shop at distribution stores with brands such as Eiger, Joven, Chomenk, and Starcross.